Protective Effect of Lactiplantibacillus plantarum subsp. plantarum SC-5 on Dextran Sulfate Sodium—Induced Colitis in Mice - Ruoran Shi; Fazheng Yu; Xueyu Hu; Yan Liu; Yuanyuan Jin; Honglin Ren; Shiying Lu; Jian Guo; Jiang Chang; Yansong Li; Zengshan Liu; Xiaoxu Wang; et al. (Foods, 2023)
Inflammatory bowel disease (IBD) is a specific immune-associated intestinal disease. At present, the conventional treatment for patients is not ideal. Probiotics are widely used in the treatment of IBD patients due to their ability to restore the function of the intestinal mucosal barrier effectively and safely. Lactiplantibacillus plantarum subsp. plantarum is a kind of probiotic that exists in the intestines of hosts and is considered to have good probiotic properties. In this study, we evaluated the therapeutic effect of Lactiplantibacillus plantarum subsp. plantarum SC-5 (SC-5) on dextran sulfate sodium (DSS)-induced colitis in C57BL/6J mice. We estimated the effect of SC-5 on the clinical symptoms of mice through a body weight change, colon length, and DAI score. The inhibitory effects of SC-5 on the levels of cytokine IL-1β, IL-6, and TNF-α were determined by ELISA. The protein expression levels of NF-κB, MAPK signaling pathway, and the tight junction proteins occludin, claudin-3, and ZO-1 were verified using Western Blot and immunofluorescence. 16S rRNA was used to verify the modulatory effect of SC-5 on the structure of intestinal microbiota in DSS-induced colitis mice. The results showed that SC-5 could alleviate the clinical symptoms of DSS-induced colitis mice, and significantly reduce the expression of pro-inflammatory cytokines in the colon tissue. It also attenuated the inflammatory response by inhibiting the protein expression of NF-κB and MAPK signaling pathways. SC-5 improved the integrity of the intestinal mucosal barrier by strengthening tight junction proteins. In addition, 16S rRNA sequencing demonstrated that SC-5 was effective in restoring intestinal flora balance, as well as in increasing the relative abundance and diversity of beneficial microbiota. These results indicated that SC-5 has the potential to be developed as a new probiotic candidate that prevents or alleviates IBD.